2021
DOI: 10.1038/s41598-021-02209-y
|View full text |Cite
|
Sign up to set email alerts
|

Excellent ballistic impact resistance of Al0.3CoCrFeNi multi-principal element alloy with unique bimodal microstructure

Abstract: Multi-principal element alloys represent a new paradigm in structural alloy design with superior mechanical properties and promising ballistic performance. Here, the mechanical response of Al0.3CoCrFeNi alloy, with unique bimodal microstructure, was evaluated at quasistatic, dynamic, and ballistic strain rates. The microstructure after quasistatic deformation was dominated by highly deformed grains. High density of deformation bands was observed at dynamic strain rates but there was no indication of adiabatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In yet another study, to achieve a good strength-ductility combination, a cold-rolled Al 0.3 CoCrFeNi alloy sample with 70% reduction was aged at 1073 K, which did impart not only a reasonably high tensile strength of ~1060 MPa, but also boosted the tensile ductility to ~26% [9]. The possibility of attaining a significant change in the structure, phase fractions and mechanical properties such as excellent impact toughness [10], wear resistance [11], fatigue resistance [12] and excellent work hardening due to twinning [13] induced as a result of Al addition, rendered the alloy system a desirable candidate for structural applications.…”
Section: Introductionmentioning
confidence: 99%
“…In yet another study, to achieve a good strength-ductility combination, a cold-rolled Al 0.3 CoCrFeNi alloy sample with 70% reduction was aged at 1073 K, which did impart not only a reasonably high tensile strength of ~1060 MPa, but also boosted the tensile ductility to ~26% [9]. The possibility of attaining a significant change in the structure, phase fractions and mechanical properties such as excellent impact toughness [10], wear resistance [11], fatigue resistance [12] and excellent work hardening due to twinning [13] induced as a result of Al addition, rendered the alloy system a desirable candidate for structural applications.…”
Section: Introductionmentioning
confidence: 99%
“…including gradient grain, [285][286][287][288][289] bimodal grain, [282,290,291] harmonic, [292][293][294][295] lamella, [296][297][298] eutectic, [299][300][301][302] and multiphase heterogeneous grain structures, [303][304][305] which are briefly reviewed as follow.…”
Section: Constructing Heterogeneous Microstructurementioning
confidence: 99%
“…Recently, constructing heterogeneous microstructure has also been proven to be an effective strategy for achieving strength–ductility synergy in FCC HEAs/MEAs, and is now becoming a very hot research topic. Figure shows diagrams of several heterogeneous structures commonly used in FCC HEAs/MEAs, including gradient grain, [ 285–289 ] bimodal grain, [ 282,290,291 ] harmonic, [ 292–295 ] lamella, [ 296–298 ] eutectic, [ 299–302 ] and multiphase heterogeneous grain structures, [ 303–305 ] which are briefly reviewed as follow.…”
Section: Novel Strategies For Achieving Strength–ductility Synergymentioning
confidence: 99%
“…Whereas the as-cast Al 0.3 CoCrFeNi HEA exhibited a tensile strength of ≈300 MPa with 60% ductility, a combination of severe cold rolling to ≈90% reduction and aging at 823 K resulted in markedly enhanced tensile strength of ≈1850 MPa with a concomitant reduction of ductility to ≈5%, essentially due to the precipitation of Al-Ni based σ and B2 precipitates [6]. Recently, Wang et al [7] reported an excellent synergy comprising tensile strength and ductility of ≈1060 MPa and ≈26%, respectively, for the Al 0.3 CoCrFeNi HEA, achieved through a cold rolling reduction of ≈70% followed by aging at 1073 K. Therefore, a careful tailoring of microstructures in Al 0.3 CoCrFeNi HEA by enabling optimized formation and stabilization of σ and/or B 2 precipitates can remarkably enhance mechanical properties, including impact toughness [8], wear resistance [9], work hardening characteristics through twinning assisted B 2 precipitation [10], and fatigue resistance [11].…”
Section: Introductionmentioning
confidence: 99%